On integrals with respect to Levy processes - Uwe Küchler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
Assume L is a non-deterministic real valued Lévy process and f is a smooth function on [0,t]
urn:nbn:de:kobv:11-10049920
Keywords: 330; Stochastischer Prozess; Analysis; Theorie